Standardization of Basic Movement â€œBelanjakanâ€ of Martial Arts on East Lombok Regency (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
Standardization of basic movements of â€œBelanjakanâ€ martial is intended to explore, develop, and preserve martial arts that grow and develop as a culture of Masbagik people of East Lombok Regency. The purpose of the study is to examine and analyze the basic movements of stance, footstep patterns, defense, and attacks